Answer:
vertical asymptote at x=2 and x=-1
Explanation:
![y= (x^2-5x)/(x^2-x-2)](https://img.qammunity.org/2020/formulas/mathematics/high-school/yh0kopqp4mziikehw1xdoa70mffmvqbo1d.png)
To find out vertical asymptote we set the denominator =0 and solve for x
![x^2 - x - 2=0](https://img.qammunity.org/2020/formulas/mathematics/high-school/kyw1wkgqia8c4uhoi0b996ld604intfwt3.png)
now factor left hand side
find out two factors whose product is -2 and sum is -1
-2 times 1 = -2
-2+1 = -1
(x-2)(x+1) =0
x-2 =0 so x= 2
x+1 =0 so x=-1
vertical asymptote at x=2 and x=-1